2006
DOI: 10.1242/dev.02325
|View full text |Cite
|
Sign up to set email alerts
|

p63 regulates multiple signalling pathways required for ectodermal organogenesis and differentiation

Abstract: Heterozygous germline mutations in p63, a transcription factor of the p53 family, result in abnormal morphogenesis of the skin and its associated structures, including hair follicles and teeth. In mice lacking p63, all ectodermal organs fail to develop, and stratification of the epidermis is absent. We show that the ectodermal placodes that mark early tooth and hair follicle morphogenesis do not form in p63-deficient embryos, although the multilayered dental lamina that precedes tooth placode formation develop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

25
272
0
3

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 243 publications
(300 citation statements)
references
References 65 publications
25
272
0
3
Order By: Relevance
“…The p63 isoforms play distinct roles in the control of epidermal development; the DNp63 isoforms are much more abundant in the epidermis compared to TAp63, which is strongly expressed in basal epidermal keratinocytes and is markedly down-regulated in the spinous epidermal layer (Laurikkala et al 2006;Romano et al 2009Romano et al , 2012LeBoeuf et al 2010;Shalom-Feuerstein et al 2011). TAp63 is also expressed in response to stresses such as wound healing (Su et al 2009b).…”
Section: The P53 Family and Its Isoformsmentioning
confidence: 99%
“…The p63 isoforms play distinct roles in the control of epidermal development; the DNp63 isoforms are much more abundant in the epidermis compared to TAp63, which is strongly expressed in basal epidermal keratinocytes and is markedly down-regulated in the spinous epidermal layer (Laurikkala et al 2006;Romano et al 2009Romano et al , 2012LeBoeuf et al 2010;Shalom-Feuerstein et al 2011). TAp63 is also expressed in response to stresses such as wound healing (Su et al 2009b).…”
Section: The P53 Family and Its Isoformsmentioning
confidence: 99%
“…TAp63 isoform expression starts at E13, and only accounts for 1% of total p63 mRNA expressed at this embryonic stage. However, TAp63 isoforms have not been detected by in situ hybridization or immunoblot; thus TAp63 protein levels appear to be barey detectable [13,20]. Studies in ES-derived cells shows that BMP-4 treatment, leading to the ectodermal fate, induces Np63, while exogenous expression of the Np63 isoform in ES-derived ectodermal cells efficiently leads to their differentiation into keratinocytes [21].…”
Section: Trp63 Gene Organization and P63 Protein Structurementioning
confidence: 99%
“…TAp63g has also been shown to activate the expression of Jagged 1 and Jagged 2, which are involved in Notch signaling, whereas Notch 1 activation has also been shown to suppress DNp63a expression, demonstrating a cross-talk between these pathways (7,8). Additional studies have shown that the biological effects of p63 in development and tumor suppression is exerted through the regulation of multiple signaling pathways (9)(10)(11)(12)(13)(14)(15)(16)(17). p73, another member of the p53 family, was also discovered based on structural similarities to p53 (18).…”
Section: Introductionmentioning
confidence: 99%